1994
DOI: 10.1073/pnas.91.23.10795
|View full text |Cite
|
Sign up to set email alerts
|

Cholera toxin B subunit: an efficient transmucosal carrier-delivery system for induction of peripheral immunological tolerance.

Abstract: Oral administration of antigens, including allergens and autoantigens, may be an efficient way to prevent disease associated with untoward immune responses to self. and non-self-antigens. However, this approach has met with limitations because it usually requires repeated administrations of large doses of antigen and is less efficient in an already immune host, and the effect is ofshort duration. We report that a single oral adinistration ofminute Oral administration of antigens is a long-recognized method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(198 citation statements)
references
References 31 publications
10
185
3
Order By: Relevance
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…administration of OVA/CTB conjugate effectively induces OVA-specific peripheral immunological tolerance, whether tested in normal BALB/c mice, OVA TCR Tg (DO11.10) mice, or in either BALB/c mice or Rag1 Ϫ/Ϫ mice transferred with OVA TCR Tg T cells. Consistent with our previous findings in other systems (17)(18)(19)(20)(21)(22), oral tolerance induction with Ag/CTB conjugate was superior to that induced with free Ag both in markedly increasing the efficacy of tolerization and in dramatically decreasing the effective amounts of Ag. The oral tolerance by i.g.…”
Section: Discussionsupporting
confidence: 91%
“…OVA protein was chemically coupled to CTB using N-succininmidyl (3-(2-pyridyl)-dithio)propionate (Pierce) as a bifunctional coupling reagent as described (17). Coupled OVA/CTB was purified and quantified by fast protein liquid chromatography (FPLC) gel filtration (Superdex 200 16/60 column; Pharmacia Biotech) using the Biologic Workstation FPLC system (Bio-Rad)).…”
Section: Conjugation Of Ova To Ctbmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being a transmucosal carrier-delivery system for induction of peripheral immunological tolerance, CTB has also been used as a nontoxic mucosal immunomodulatory adjuvant through its binding ability to the asialo-GM-1 receptor on B cells, T cells and DCs. 51 Smits et al found that intratracheal administration of CTB can suppress allergic inflammation through the induction of airway luminal IgA secretions in a TGF-b-dependent manner, which is necessary for its preventive and curative effect. 52 CpG oligodeoxynucleotides (CpG ODNs).…”
Section: Antigen Dose and Formulationmentioning
confidence: 99%
“…Sun et al 51 found that using N-suc-cinimidyl [3-(2-pyridyl)dithio]-propionate as a conjugator to link different antigens can achieve immunotolerance through a single oral administration of low-dose antigen. In a study of the HDM allergen, Lee and Mo found that immune tolerance could be induced through intranasal application of a HDM and CTB conjugate in the murine allergic rhinitis model and that the effect can last for 4 weeks.…”
Section: Ctb-agmentioning
confidence: 99%